Severe Tuberculosis Requiring Intensive Care: A Descriptive Analysis - Raquel Pacheco Duro; Paulo Figueiredo Dias; Alcina Azevedo Ferreira; Sandra Margarida Xerinda; Carlos Lima Alves; António Carlos Sarmento; Lurdes Campos dos Santos (Critical Care Research and Practice)
Background. This study aims to describe the characteristics of tuberculosis (TB) patients requiring intensive care and to determine the in-hospital mortality and the associated predictive factors. Methods. Retrospective cohort study of all TB patients admitted to the ICU of the Infectious Diseases Department of Centro Hospitalar de São João (Porto, Portugal) between January 2007 and July 2014. Comorbid diagnoses, clinical features, radiological and laboratory investigations, and outcomes were reviewed. Univariate analysis was performed to identify risk factors for death. Results. We included 39 patients: median age was 52.0 years and 74.4% were male. Twenty-one patients (53.8%) died during hospital stay (15 in the ICU). The diagnosis of isolated pulmonary TB, a positive smear for acid-fast-bacilli and a positive PCR for Mycobacterium tuberculosis in patients of pulmonary disease, severe sepsis/septic shock, acute renal failure and Multiple Organ Dysfunction Syndrome on admission, the need for mechanical ventilation or vasopressor support, hospital acquired infection, use of adjunctive corticotherapy, smoking, and alcohol abuse were significantly associated with mortality (p<0.05). Conclusion. This cohort of TB patients requiring intensive care presented a high mortality rate. Most risk factors for mortality were related to organ failure, but others could be attributed to delay in the diagnostic and therapeutic approach, important targets for intervention.